Modelling of the combustion process of methane (CH4) in the software package PrIMe (Journal of Mathematics Mechanics and Computer Science, 2018)
Modeling of methane combustion in air carried out in environment modeling of chemical processessoftware package Process Informatics Model (PrIMe). To investigate the methane combustion inair in a program PrIMe was chosen mechanism GRI 3.0, which describes burning of methane andother hydrocarbons (acetylene, propane). Kinetic mechanism GRI 3.0 describe the reactions takingplace at the molecular level, which deals with the order in which communications are broken orformed. The mechanism chosen from base of the PrIMe program consists of the 309th reactionand 53 reagents, and also for modeling of burning Plug Flow Reactor (PFR), the reactor of idealreplacement, has been chosen stoichiometric mix of burning of methane in air. Modeling methaneinlet combustion air at a low pressure can be seen that almost no chemical reactions occur, but withincreasing temperature the reaction proceed faster also can be seen that the fuel in the pyrolysisof nitrogen containing radicals leads to the formation of nitrogen oxides NOx
Keywords: methane; PrIMe software system; combustion mechanism; stoichiometry; combustion rate